Technology-led sustainable arid fruit production in rainfed situation - Meghwal, P R; Singh, Akath (Indian Horticulture, 2020)
During recent times, the whole globe is facing problem of climate change and its impact on agricultural production. Fruit crops like ber, lasora (gonda), karonda and khejri can be grown under arid and semi-arid situation as rainfed or with supplementary irrigation from harvested rainwater during establishment and other critical stages. Recent technological intervention in these indigenous fruit-cum vegetables crops are being discussed.